Analysis of the Ribonuclease A Superfamily of antimicrobial peptides in patients undergoing chronic peritoneal dialysis - Pottanat, Neha Dhingra; Bartosova, Maria; Schmitt, Claus P. (Scientific reports, 2019)
Infectious peritonitis is a common complication in patients undergoing chronic peritoneal dialysis (PD), limiting the duration of PD as a modality for renal replacement therapy and increasing patient morbidity and mortality. Antimicrobial peptides (AMPs) serve critical roles in mucosal defense, but their expression and activity during peritonitis are poorly understood. We hypothesized that AMPs belonging to the Ribonuclease (RNase) A Superfamily are present in peritoneal fluid and increase during peritonitis in patients undergoing chronic PD. In the absence of peritonitis, we detected RNase 3, RNase 6, and RNase 7 in cell-free supernatants and viable cells obtained from peritoneal fluid of chronic PD patients. The cellular sources of these RNases were eosinophils (RNase 3), macrophages (RNase 6), and mesothelial cells (RNase 7). During peritonitis, RNase 3 increased 55-fold and RNase 7 levels increased 3-fold on average, whereas RNase 6 levels were unchanged. The areas under the receiver-operating characteristic curves for RNase 3 and RNase 7 were 0.99 (95% confidence interval (CI): 0.96-1.0) and 0.79 (95% CI: 0.64-0.93), respectively, indicating their potential as biomarkers of peritonitis. Discrete omental reservoirs of these RNases were evident in patients with end stage kidney disease prior to PD initiation, and omental RNase 3 reactive cells increased in patients undergoing PD with a history of peritonitis. We propose that constitutive and inducible pools of antimicrobial RNases form a network to shield the peritoneal cavity from microbial invasion in patients undergoing chronic PD.
Gesehen am 26.11.2019